SYNTHESIS, ANTITUMOR ACTIVITY, PHARMACOPHORE MODELING AND QSAR STUDIES OF NOVEL PYRAZOLES AND PYRAZOLO [1, 5-A] PYRIMIDINES AGAINST BREAST ADENOCARCINOMA MCF-7 CELL LINE - Ismail, Magda M. F.; Soliman, Dalia H.; Farrag, Amel M.; Sabour, Rehab (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The present work aimed to synthesize New series of pyrazoles 3 and pyrazolo[1,5-a]pyrimidines 5, 7, 9 in order to evaluate their antiproliferative activity against human breast adenocarcinoma MCF-7cell line and study the cell cycle progression of the most active compounds. In addition, Pharmacophore modeling and QSAR Studies of these new compounds were done. Methods: The diazonium salt of 4-aminoacetophenone 1 was coupled with malononitrile in ethanol using sodium acetate affords 2-[(4-acetylphenyl)diazenyl] malononitrile Cycloaddition of hydrazine hydrate, in molar ratios 1:1 or 1:2, on compound 2, furnished 3,5-diaminopyrazolederivatives 3a and 3b respectively. Moreover, new pyrazolo[1,5-a]pyrimidine derivatives 5a-f were obtained upon cyclocondensation of 3a, b with different chalcones 4a-c in EtOH/piperidine,while compounds 7a-f were prepared via cycloaddition of 3a, b with various arylidene malononitriles 6a-c in the same reaction condition. Finally, treatment of 3a, b with ethyl 2-cyano-3-ethoxyacrylate 8a or 2-(ethoxymethylene)malononitrile 8b in EtOH/TEA yielded the novel pyrazolo[1,5-a]pyrimidine derivatives 9a, b respectively. These target compounds were screened for their cytotoxic activity against MCF-7 (human breast Cell Line) followed by study cell cycle of 7a. Finally, Pharmacophore modeling and QSAR Studies was carried out. Results: The pyrazolopyrimidine 7a was the most active compound (IC50 = 3.25 ÂµM), whereas, some of the tested compounds exploited moderate growth inhibitory activity. Its effect was further studied on cell cycle progression; results showed that compound 7a induced cell cycle arrest at S-phase verifying this compound as a promising selective anticancer agent. Conclusion: Compound 7a was found to be the most active member against MCF-7 breast cancer (IC50= 3.25 Î¼M), Further biological assessment of 7a using flow-cytometric analysis, revealed that it induced cell cycle arrest at S phase. Keywords: Pyrazole, Pyrazolo[1,5-a]pyrimidine, MCF-7 breast cancer cell line, Cell cycle profile, 3D pharmacophore,1 QSAR study